The Effect of Multi Channel Marketing Strategy and Market Logistics toward the Improvement of MSMEs’ (Micro, Small and Medium Enterprises) Sales during Covid-19 Pandemic (Research Study on Food and Drink Accommodation MSME in East Java) - MG Wi Endang; Sri Mangesti Rahayu; Zahroh Z.A; Gunawan Eko Nurtjahjono; Dewi Noor Fatikhah Rokhimakhumullah (JPAS (Journal of Public Administration Studies), 2022)
MSMEs have a large opportunity for Indonesia state revenue. The momentum of covid 19 pandemic can be used by MSMEs to digitally transform, so they can enter the digital marketplace and become part of national and global supply. MSMEs must be able to adapt to existing business developments and they will be more directed to digital. They no longer playing at a conservative level but must be able to see digital opportunities so that they can target a wider market. This study uses a quantitative analysis that has never been proposed, as well as being the novelty of this research. The sample was taken from MSMEs that had the most impact during the Covid-19 pandemic, which is the business of providing food and beverage accommodation located in the city of Surabaya and the city of Malang. Multi Channel and Market Logistics have a positive and significant impact to increase MSME sales in the Covid-19 Pandemic Era.